The relationship between personality and the oral practice of english outside the classroom among students of avanced intensive english I, on the second semester of 2012 at the Foreign Language Department in the University of El Salvador - Arévalo Ramos, Isabel Cristina
English is a language that over the years has increased its popularity, since it is spoken in many countries around the world. It is well recognized as a lingua franca among many countries, given that roughly, only one out of every four users of English in the world is a native speaker of the language (Crystal, 2003). With the development of global communication, the importance of knowing a second language is increasing considerably, this is the reason why teachers and students ask themselves on how to prepare to acquire a better level of oral English, to reach a professional goal in their lives. Without a doubt, this is a great challenge that students and teachers of English as a Foreign Language have to face.